2021
DOI: 10.1088/1757-899x/1046/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stirring time on ZnO nanoparticles properties and morphology

Abstract: The impact of stirring time on the ZnO nanoparticles assembly and properties as a novel study was investigated. A precipitation technique has been used for synthesizing ZnO nanoparticles and the impact of stirring time as well as calcination temperature and time were analyzed. X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and Fourier-transform infrared spectroscopy (FTIR) were used for characterizing the resulting powder. The effect of stirring time, (viz., 0, 2, 4 and 6 h), on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The peaks at 620.2, 1370.0 cm −1 and around 840.0 cm −1 corresponds ZnO stretching bonds. These frequencies for metal oxides match with the earlier reported in literature [27]. The FTIR of synthesised ZnO powder and the one coated on ZK60alloy shows that both spectra are almost similar except for a minor peak change showing that the interatomic bonding remains intact during the coating process.…”
Section: Characterisation Of Zno Powder and Zno Deposited Mg Alloy Su...supporting
confidence: 89%
“…The peaks at 620.2, 1370.0 cm −1 and around 840.0 cm −1 corresponds ZnO stretching bonds. These frequencies for metal oxides match with the earlier reported in literature [27]. The FTIR of synthesised ZnO powder and the one coated on ZK60alloy shows that both spectra are almost similar except for a minor peak change showing that the interatomic bonding remains intact during the coating process.…”
Section: Characterisation Of Zno Powder and Zno Deposited Mg Alloy Su...supporting
confidence: 89%
“…This finding is consistent with several previous studies that also demonstrated agglomeration of spherical-shaped ZnO nanoparticles on SEM micrographs [ 27 , 28 ]. The morphology of ZnO nanoparticles could be altered with numerous factors, including temperature change [ 29 ] and stirring time during synthesis [ 30 ]. In the present study, ZnO was commercially acquired; hence, the reason for observing spherical-shaped agglomerated nanoparticles cannot be understood.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, its antibacterial properties, [28] nontoxic material that is safe for humans and animals, [29] high chemical and mechanical stability, [30] high catalyses activity, [31] it has a wide range of radiation absorption, [32] electrochemical coupling coefficient, [32c,33] heat stability, high selectivity and durability. [34] It has been widely used in different fields, including the food, pharmaceutical and cosmetic industry, coating and paints, textile, rubber, electronics and electrotechnology industries. [32c,35] Because the adsorbent must be eco-friendly, non-toxic, abundant and inexpensive, the red clay and ZnO nanoparticles were selected for this study given their advantages.…”
Section: Introductionmentioning
confidence: 99%